La improvisación teatral como herramienta potenciadora de habilidades en un comunicador audiovisual - Leo Hernández, Gonzalo Alonso (2022)
This research work makes an analysis of how the practice of theatrical improvisation technique can enhance the skills of an audiovisual communicator. What motivated the development of the study is the usefulness represented by the practice of theatrical improvisation applied conscientiously in the work of the audiovisual communicator. This profession involves constant and strenuous creative processes, however, it is not always taken into account that creativity is a human capacity that requires constant training and this research aims to understand how the theatrical improvisation technique contributes to the development of the activity professional of an audiovisual communicator. The methodology used in this research is qualitative, since it responds to the collection of information about the behavior and perception of people in order to affirm the theory embodied in the research topic. The data will be collected through in-depth and semi-structured individual interviews with a sample of experts, made up of filmmakers, creators, producers, screenwriters, directors who apply improvisation in their professional activity and also through focus groups, directed to a sample homogeneous conformed by students of last cycles and recent graduates of the communications career specialized in the audiovisual field and who practice and develop the theatrical improvisation technique. The research considers it important that the student and the audiovisual communication professional have an approach to theatrical improvisation and thus, enhance their skills to apply them in the workplace.